Pengaruh Pajak, Mekanisme Bonus, dan Tunneling Incentive Terhadap Keputusan Transfer Pricing Pada Perusahaan Manufaktur Periode 2017-2019 - Jannah, Fathul; Sarwani, Sarwani; Novriyandana, Rifqi; Hardi, Enny (Universitas Pendidikan Indonesia, 2022)
This study aims to examine and to analyze: (1) the effect of tax on transfer pricing decisions, (2) the effect of bonus mechanism on transfer pricing decisions, (3) the effect of tunneling incentive on transfer pricing decisions in manufacturing companies in the basic industry and chemical sector listed on The Indonesian Stock Exchange for the period of 2017-2019. The population in this study were 67 the basic industry and chemical manufacturing companies listed on The Indonesian Stock Exchange for the period of 2017-2019. The study sample consisted of 16 companies. The sampling method in this study was a non-probability sampling method with purposive sampling technique which resulted in 48 samples from 16 companies period 2017-2019. The data obtained were secondary data by collecting annual reports of manufacturing companies in the basic industry and chemical sector listed on The Indonesian Stock Exchange.The analysis technique was logistic regression analysis technique. The results of this study indicate that tax and bonus mechanism have no effect on transfer pricing decisions, while tunneling incentive affects transfer pricing decisions. The implications of this research are expected to be useful for theory and knowledge developers, as well as input and consideration for the government, companies, investors, and other stakeholders.